THE RELATIONSHIP OF KNOWLEDGE AND FAMILY HEAD'S BEHAVIOR IN ERADICATION OF MOSQUITO NESTS (PSN) IN DENGUE HEMORRHAGIC FEVER ENDEMIC AREAS MUARA DUA HEALTH CENTER, LHOKSEUMAWE CITY - Putra, Eridha Putra; Maulida; Simbolon, Roma Julinawati (Aceh Sanitation Journal, 2022)
Dengue Hemorrhagic Fever (DHF) or Dengue Hemorrhagic Fever (DHF) is currently a public health problem in Indonesia, prevention efforts that can be done are to break the chain of transmission of DHF, one of which is through the Eradication of Mosquito Nests (PSN). DHF by all levels of society.This study aims to determine the relationship between knowledge and behavior of the head of the family in Eradicating Mosquito Nests (PSN) in 3 DHF Endemic Areas at the Muara Dua Health Center, Lhokseumawe City.The type of research used is analytic with a cross-sectional design. The population and sample of this study are all heads of families who live in3 Dengue Endemic Areas Muara Dua Public Health Center, Lhokseumawe City with a total sample of 98 house holds with simple random sampling technique.The results of the research on the characteristics of respondents based on the age of the majority were 36-45 years 53 respondents, the sex of the majority was male 96 respondents, the education of the majority was high school 51 respondents, the majority of jobs were non ASN 81 respondents. The highest KK knowledge in the sufficient category is 47 respondents, the highest KK behavior is in the good category, 69 respondents. Statistical test results show there is a relationship between knowledge and the behavior of the head of the family in 3 DHF Endemic Areas at the Muara Dua Community Health Center, Lhokseumawe City where a ρ value of 0.000 (below the alpha (α) value of 0.05) is obtained so that Ha is accepted. Based on the results of this study, it is suggested to the health center to be able to improve health education to the community, especially heads of families about PSN.